The Efficacy of Using Reciprocal Teaching Technique in Teaching Reading to Indonesian English as Foreign Language (EFL) Students - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2020)
This research aims at finding out the efficacy of using reciprocal teaching technique in teaching reading to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of reciprocal teaching technique effective in teaching reading to Indonesian EFL students?. The research can be an addition in the persisting teaching reading by using reciprocal teaching technique. This research was conducted at the tenth grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with pre-test and post-test design. The pre-test was given to find out the basic ability of the students in reading and the post-test given to find out the students’ improvement in reading after giving the treatment by using of reciprocal teaching technique. The findings show that using reciprocal teaching technique is effective in teaching reading to Indonesian EFL students. It is supported by the result of significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use reciprocal teaching technique in developing reading skill of Indonesian EFL students.